A case study into pupil perceptions of Latin, conducted with a mixed-ability Year 9 Latin class at a comprehensive faith school. Issue 43 (2021) - Bennett, David
Abstract : This case study was prompted by the identification, in observations and in discussion with the normal class teacher, of pupil demotivation and disaffection during Latin lessons, and the fact that this represented a considerable barrier to attainment and progress. My observation of this phenomenon coincided with Year 9 submitting their GCSE options. The combination of apparently ambiguous attitudes towards the subject and the fact that these attitudes were being brought to the fore explicitly because of the options choices drew my attention to pupil perceptions of the subject. It seemed to me that understanding the way in which pupils perceive the subject might be instructive for my own teaching practice, allowing me to better understand what pupils enjoy about the subject, what they find difficult, what enthuses them and what turns them off. Furthermore, the place of Latin within schools in general, and the particular school in which I conducted this study, is not something that should be taken for granted. It seemed to me, therefore, that this case study might provide some insight into whether Latin is a subject that young people feel is relevant and perhaps might offer some insight into what can allow Latin to have as inclusive an appeal as possible.